Endoscopic therapy of oesophageal strictures in children – a multicentre study - Pieczarkowski, Stanisław; Woynarowski, Marek; Landowski, Piotr; Wilk, Robert; Daukszewicz, Adam; Toporowska-Kowalska, Ewa; Albrecht, Piotr; Ignys, Iwona; Czkwianianc, Elżbieta; Jarocka-Cyrta, Elżbieta; Korczowski, Bartosz (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Introduction: Oesophageal strictures are rare in children but may require endoscopic dilation. Aim : To gather information on centres performing endoscopic oesophageal dilation in Poland. Material and method s: The data were obtained from questionnaires concerning the relevant data mailed to 22 paediatric endoscopy centres. Completed questionnaires were received from 11 centres. Results : In 2010 the 11 Polish paediatric endoscopy centres performed a total of 10,650 endoscopic procedures. This included 347 oesophageal dilations in 106 paediatric patients aged from 1 month to 18 years. The numbers of patients treated at individual centres ranged from 2 to 40. The indications for oesophageal dilation were as follows: postoperative strictures in 68 children, oesophageal burns in 17 children, postinflammatory strictures in 14 children, achalasia in 4 children, and strictures caused by a foreign body in 3 children. Rigid guidewire dilators were used in the majority of procedures (271), rigid dilators without a guidewire in 32 procedures, and balloon dilators in 45 procedures. A total of 203 procedures were conducted under fluoroscopic guidance, and 144 without the use of fluoroscopy. The number of dilating sessions performed in individual children varied from 1 to 6 and more. Conclusions : Oesophageal dilation constituted a minor proportion of all paediatric endoscopic procedures. The majority of children requiring dilation were patients up to 3 years of age with postoperative oesophageal strictures. In the majority of the centres rigid guidewire dilators were used, and in one third of the procedures these dilators were introduced without fluoroscopic guidance.